Prospecção do lodo de ETE com capim elefante e óleo de cozinha residual como alternativa energética a produção de pellets - Almeida, Carlos André Silvestre Medeiros de (2020)
Correct destination of wastes is extremely important to society and the environment. To reach this goal new researches for reuse of these wastes are convenient. The use of pellets has spread for this purpose, providing energy alternatives with satisfactory results. The propose of this work was to determinate the elemental, chemical and energetic features of pellets productize from sewage plant sludge gather with elephant grass and kitchen oil waste to energy conception, also apply torrefaction technique for the purpose of gain calorific power. Different proportions were adopted, 25% and 50% for sludge and 75% and 50% for grass. The parameters of moisture, bulk density, elemental composition, immediate chemical analysis (ash, volatile and fixed carbon content), calorific value, fines content, strength, and mechanical durability were analyzed. Pellets with a proportion of 50% of sludge showed lower calorific value with values of 13.56 and 13.87 MJ / kg and higher ash content reaching values of 16.51%, but greater bulk density (705 e 682 kg/m³), greater resistance (28.70 e 29.75 kgf/cm²) and durability mechanics (99.59 e 99.89%) and less fine content (both 1%). The oil provided an increase in calorific value of up to 2.66% in the pellets, as well as the torrefaction technique with an increase reaching up to 6.63%. The pellets presented values according to parameters determined by the standard of pellets EN 14961-6, with the exception of pellets with 50% of sludge that in the ashes had values greater than the minimum foreseen in the standard.